WAYS TO DEVELOP CRITICAL THINKING ABILITIES OF FOREIGN LANGUAGE LEARNERS (Academicia Globe: Inderscience Research, 2022)
This article deals with one of the most essential issues in methodology. Everyone agrees that if a language learner masters good critical thinking ability he or she will not face any challenge in using a language skill. As we produce a foreign language data our speaking or writing materials are based on our thinking abilities. When one faces with the disputable theme to discuss he should ponder over that issue to express his or her ideas to the listener. Critical thinking abilities help a foreign language learner to ponder over the issue by categorizing, identifying the main concept, by discussing it objectively based on his or her previous knowledge. Modern methodology requires teachers to be able to boost learners’ critical thinking abilities in order to form easy flowing of information in the process of using the language. There are some steps and ways how teachers can form or develop critical thinking abilities of their learners, how they themselves can enhance their abilities. It is not so difficult to teach or involve them into activities that demand using critical thinking ability, the main issue is to help them to get out of the box.